DOES THE STUDY PROGRAM AFFECT THE KIND OF MULTIPLE INTELLIGENCES? - Sugiarni, Rani; Azmy, Dara Septia; Rahmi, Dini Fauziyanti; Apriliani, Sundari (SIGMA DIDAKTIKA: Jurnal Pendidikan Matematika, 2021)
Gardner divides into Everyone has 8 types of intelligence, namely linguistic, logical-mathematical, musical, kinesthetic, spatial, interpersonal, intrapersonal, and naturalistic intelligence. Each individual has 8 types of intelligence, but depending on which type is the most dominant. The purpose of this study is to find out how the influence of taking a study program during the period a student runs his lectures on the type of multiple intelligences possessed by each student who acts as a respondent in this study. The method used by the researcher is descriptive quantitative and uses a cross-sectional design with 32 subjects. Inclusion criteria: students who are willing to take part in the research. Each respondent was asked to fill out a questionnaire about multiple intelligences that had been provided by the researcher. Most of the respondents are 19 years old (40%) and (62.5%) respondents have continuity between the study program and the type of multiple intelligence they have. Respondents with study programs that are not sustainable with the type of intelligence they have (37.5%), there are facts which state that the study program significantly affects the type of multiple intelligences.